THE DECAY OF THE RUSSIA-EU ENERGY DIALOGUE MECHANISM FROM A ROLE PERSPECTIVE - Weichao , Shu (PEOPLE: International Journal of Social Sciences, 2024)
The energy issue is at the core of the interaction between Russia and Europe. This paper, based on the perspective of role theory, systematically reviews the evolution of the Russia-Europe energy dialogue mechanism in the post-Cold War era. It combines role positioning and role expectations as two core variables to analyze the influencing factors of the Russia-Europe energy dialogue mechanism. Therefore, six influencing factors are summarized, including political culture, energy strategy, and energy groups related to role positioning, as well as historical traditions, international crises, and energy revolutions related to role expectations. The paper argues that the evolution of the Russia-Europe energy dialogue mechanism exhibits three characteristics: firstly, consistency with Russia-Europe relations; secondly, idealism in role expectations formed due to political cultural differences; and thirdly, the constraining nature of the asymmetrical structure on energy cooperation. Consequently, the Russia-Europe energy dialogue mechanism is in a state of stagnation, and Russia-Europe energy cooperation is showing a fragmented trend.